Novel agents in mantle cell lymphoma. Issue 6 (3rd June 2017) - Tucker, David; Rule, Simon
ABSTRACT: Introduction : Mantle cell lymphoma (MCL) usually takes an aggressive clinical course and carries a poor prognosis. Recently, progress has been made in the treatment of MCL including the development of a number of novel agents which target intracellular pathways and the extracellular microenvironment. These agents have transformed the landscape of available therapeutic options. Areas covered : The current literature on the novel agents which currently hold a licence for the treatment of MCL in the context of front-line therapy and in the relapsed/refractory setting is summarized. In addition, targeted therapies showing promise at an earlier stage of development will also be discussed. A literature search was performed using the terms 'mantle cell lymphoma', 'bortezomib', 'temsirolimus', 'lenalidomide', 'ibrutinib', 'novel agents', 'targeted molecular therapies' and derivations thereof. Expert commentary : In addition to improvements in immunochemotherapy, a succession of new molecular targets and corresponding drugs has revolutionised MCL therapy. The discovery of a novel agent which disrupts external signalling pathways through inhibition of Bruton's tyrosine kinase has been a particularly exciting breakthrough. The best way to sequence and combine these agents with existing regimens and how to overcome the problem of drug resistance represent new challenges in this rapidly developing field.